2018
DOI: 10.1080/0284186x.2018.1521986
|View full text |Cite
|
Sign up to set email alerts
|

Survival and prognostic factors of pulmonary oligometastases treated with stereotactic body radiotherapy

Abstract: Background: Stereotactic body radiotherapy (SBRT) for pulmonary oligometastatic disease achieves excellent treatment outcomes in terms of local control and toxicity. Patients treated with SBRT are often elderly and have multiple co-morbidities. This subset of patients may experience different survival as compared to young and fit patients subjected to radical metastasectomies. The purpose of this retrospective study was to evaluate OS and identify factors associated with OS for inoperable pulmonary oligometast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 33 publications
5
38
0
2
Order By: Relevance
“…The 1-, 2-year LC and OS rates for the entire cohort were 82, 70 and 84%, 71%, respectively. Our findings are comparable with the current findings in the literature (Table 7) [8][9][10][11][12][13][14][15][16].…”
Section: Discussionsupporting
confidence: 93%
“…The 1-, 2-year LC and OS rates for the entire cohort were 82, 70 and 84%, 71%, respectively. Our findings are comparable with the current findings in the literature (Table 7) [8][9][10][11][12][13][14][15][16].…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are comparable with the current findings in the literature (Tab. 7) (8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…A locoregionally controlled primary tumour is not a precondition but should be considered a prognostic parameter which is critical to report specifically. Some studies reported a better prognosis for metachronous OMD [28,86], but this was not consistently observed [25,74]. Though both synchronous and metachronous metastases are considered OMD, the prognosis, options for treatment and risk of occult disseminated metastases of these patients can differ, with the length of the DFI appearing to have a prognostic impact [46,69,87].…”
Section: Oligo-progressionmentioning
confidence: 99%